2018
DOI: 10.3892/ijo.2018.4453
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin activation by resveratrol inhibits the proliferation and metastasis of colorectal cancer cells

Abstract: Resveratrol (RSV) is a polyphenolic compound that naturally occurs in grapes, peanuts and berries. Considerable research has been conducted to determine the benefits of RSV against various human cancer types. Tristetraprolin (TTP) is an AU-rich element-binding protein that regulates mRNA stability and has decreased expression in human cancer. The present study investigated the biological effect of RSV on TTP gene regulation in colon cancer cells. RSV inhibited the proliferation and invasion/metastasis of HCT11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
(71 reference statements)
0
26
0
Order By: Relevance
“…Resveratrol suppressed the proliferation and invasion/metastasis of colorectal cancer cells by activating TTP [39].…”
Section: Pd-l1mentioning
confidence: 98%
“…Resveratrol suppressed the proliferation and invasion/metastasis of colorectal cancer cells by activating TTP [39].…”
Section: Pd-l1mentioning
confidence: 98%
“…In addition, by suppressing the expression of lin-28 homolog A (Lin28A), TTP can increase the expression of the tumor suppressor microRNA (miRNA) let-7, whose expression is negatively regulated by Lin28A [ 29 , 55 ]. The miRNA let-7 has been implicated in the regulation of gene transcription including high mobility group A2 (HMGA2) [ 56 ].…”
Section: Oncogenes and Tumor Suppressor Genes Subjected To Ttp-medmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors in colorectal cancer cells induce TTP expression through activation of EGR1, which promote its binding affinity to ARE, and thus, reduce cell growth and angiogenesis [ 118 , 119 ]. Resveratrol, a natural polyphenolic compound present in many plant species, including grapes, peanuts, and berries, inhibits cell growth through TTP upregulation in several cancers, including breast [ 142 ], colorectal [ 29 ] and brain cancer [ 74 ]. Molecular activators of PP2A enhance the anti-inflammatory function of TTP in lung cancer cells, and thus, provide pharmacotherapeutic strategies to chronic inflammation-mediated cancer [ 133 ].…”
Section: Regulation Of Ttp Expression In Normal and Cancer Cellsmentioning
confidence: 99%
“…Accumulating evidence has shown that natural plant compounds (NPCs), such as curcumin, resveratrol and dictamnine, have significant clinical benefits in cancer, such as inhibiting cell proliferation, affecting the cell cycle, and promoting apoptosis and/or autophagy (6)(7)(8). In addition, bioactive natural components extracted from plants have received attention for their inhibition of epithelial-mesenchymal transformation (EMT) through anti-inflammatory, anti-fibrosis or anti-oxidant mechanisms (9).…”
Section: Introductionmentioning
confidence: 99%